(untitled) (Docentes 2.0 Journal, 2020)
This research presents gamification as an innovative technology that the teacher can apply in the subjects of the higher educational level, with the purpose of increasing the interest of the students in the study, and what to see reflected in the academic performance of the university students. The advancement of game and training technology has brought education in such a way that currently the teacher has to find strategies and tools for the most interesting sea learning process for students. That is why, with this objective, the investigation of different current gamification tools with impact in the classroom was carried out as an effective strategy for learning the subjects. The qualitative approach allows us to apply a documentary-bibliographic research, facilitate the review and comparison of three tools, determine what offers the greatest benefits, both to teachers and students, therefore, it is concluded that the tool called Quizizz is the most Complete The use of this tool, hand in hand with the creativity of the teacher in the design of dynamic activities as a game, improves the performance and results of the students in the subjects. However, it must be considered that the efficiency measure of the affected results does not only depend on the tools, other factors that may affect these results.